Framework for assessing technological innovation capability in research and technology organizations - Mortazavi Ravari, Sara Sadat; Mehrabanfar, Ehsan; Banaitis, Audrius; Banaitienė, Nerija (Journal of Business Economics and Management, 2016)
This study aims to evaluate technology innovation capabilities (TICs) of research and technology organizations (RTOs) by applying Fuzzy-DEMATEL & ANP techniques, in order to provide a practical lookout for their firm’s requirement in this regard. Based on literature review, six main criteria and eighteen sub-criteria are extracted. Fuzzy-DEMATEL is applied to analyze the casual relationships among the criteria and subcriteria. After identifying the relations between the criteria a questionnaire is developed and distributed among sixteen experts to assess the validity of the questionnaire, then the relations are weighted by ANP. It is concluded that proposed model is a comprehensive model that integrates qualitative and quantitative approaches to develop a step by step model to reach to the main TICs criteria in RTOs. Although, there are many previous researches illustrating various models to evaluate TICs, there is no formidable one using these techniques combination. Based on the abilities of the techniques and the results emerged this paper has prepared a robust model available for other RTOs to adopt as a true reference to reach to their TICs.